It's not the same thing: considering a path forward for teaching public speaking online. Issue 2 (2nd July 2016) - Ward, Susan
ABSTRACT: Teaching public speaking online is both an innovative and experimental approach that has created dissonance within the discipline. By definition, the online public speaking course is not the same thing as the face-to-face course. This essay considers the status of the online course and addresses concerns about teaching the traditional course online including how it is conceptualized and designed. Should we teach nearly the same thing but not the same thing online? This question is addressed by considering two different paths for moving forward: not calling the online course the same thing and calling the online course the same thing. The author argues in favor of a path forward that advocates for the creation of a new course altogether—one focused on speaking in digital contexts.